Generalized Beauty: The Sum of the Numbers in a Hockey Stick on the Pascal’s Triangle** - เอี่ยมพันธ์ ผู้ช่วยศาสตราจารย์ ดร.อัยเรศ; ทนะมูล กัลยา; พระสงฆ์ อัจฉรา (Journal of Food Health and Bioenvironmental Science, 2016)
The purpose of this study was to find a general form of the sum of the numbers in a hockey stick on Pascal’s triangle. The results demonstrate that the general form of the sum of the numbers in the handle of the hockey stick, with slots and starting from the left in the N+1 row on Pascal’s triangle is equal to where n and m are integers with and 0" src="https://latex.codecogs.com/gif.latex?m>&space;0"> Moreover, the sum of the numbers in the handle of the hockey stick, starting from the left and right on the Pascal’s triangle, are equal.